Ictal epileptic headache in young female - Tiwari, Priyal; Renjen, Pushpendra Nath; Chaudhari, Dinesh Mohan (International Journal of Advances in Medicine, 2023)
The establishment of a temporal association between a hybrid of headache and epilepsy is essential for correct diagnosis and management of headache. Epilepsy-associated headaches (such as migralepsy, hemicrania epileptica, post ictal headache and ictal epileptic headaches) may be similar to the patients’ usual headache or may be a new type of headache. The location of headaches is unrelated to the EEG localization of epileptic aura or ictal discharges. The only established association of location of headaches and epilepsy is seen in cases of migraine with a visual aura which seems to precede few instances of occipital epilepsy. EEG helps to distinguish epileptic headache from non-epileptic headache during ictus (convulsive or non-convulsive). Hemicrania epileptica is a rare type of EEG-demonstrated ictal epileptic headache characterized by migrainous features (such as unilateral, throbbing pain associated with nausea, vomiting, scintillating scotomas, and flashing lights) occurring during an ictal EEG. We should watch for migrainous visual auras (flashing lights and scintillating scotomas) and distinguish them from occipital lobe seizures (aura including visual hallucinations) with the help of clinical features and simultaneous demonstration of ictus on EEG. We report a case of a 28-year-old female presenting with a new headache as a sole feature of posterior lobe non-epileptic seizure. Early diagnosis of painful seizures leads to timely treatment of the episodic headaches using anti-epileptic therapy.